Montana Rural Education Curriculum Guide - Kroon, Ralph, Comp. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
The material in this K-8 curriculum guide is designed to provide classroom professionals in rural Montana schools with some guidance as to when to introduce and develop concepts in each subject area. It is intended to be a guide, not a rule book or complete course of study. For each subject area and for each grade level, topics are coded as I (introduced), D (developed), M (mastered), R (reviewed, reinforced), or E (extended, expanded). Topics are defined (where necessary) and their component parts are listed separately. Topics include Reading (readiness skills, word recognition, comprehension skills, study skills), English Language Arts (oral, written, visual, media hardware--where equipment is available), Mathematics (numeration, money, basic facts and computation, fractions, decimals, ratio-proportion, percent, number theory, measurement, geometry, statistics, integers, algebra), Science (life science, plants, microorganisms, environment, physical science, earth and space science), Social Studies (school, home and family living, communities and their helpers, holidays and seasons, transportation and communication, geography, citizenship and government, history), Music (singing, playing, rhythm, theory, listening), Health (aging, use and misuse of substances, personal health, community health, consumer health, mental-emotional health, disease control and prevention, family life and human sexuality, nutrition, health-safety education), and Physical Education (psychomotor, affective, and cognitive domains). (BRR)
ERIC Note: Also compiled by the Montana Rural Teachers, Montana County Supervisors and Montana Office of Public Instruction.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Guides; Elementary Education; Health; Language Arts; Mathematics; Music; Physical Education; Reading; Rural Education; Sciences; Sequential Approach; Social Studies; Spiral Curriculum; Montana; Guides, Classroom -- Teacher